Caracterização Citogenômica de Passeriformes e Charadriiformes: Uma Análise da Evolução Cariotípica na Estrutura Organizacional dos Microcromossomos das Aves - Souza , Marcelo Santos de (2024)
Birds have long been subject of human admiration and fascination for their remarkable diversity in many ways, these creatures offer crucial insights into the evolution of life on Earth. From their most primitive forms to modern ones, the evolutionary history of birds reflects a wide range of adaptive processes over millions of years. Birds are distributed across a wide variety of environments, from continental lands to marine ecosystems, demonstrating their extraordinary capacity for evolution and adaptation. Despite significant advances in recent decades, the understanding of the genomic organization and karyotypic evolution of birds is still limited. To address these issues, different techniques, including classical and molecular cytogenetics, have been employed. Birds have a bimodal karyotype, made up of two distinct groups of chromosomes: macrochromosomes and microchromosomes. The presence of these microchromosomes represents a challenge for cytogenetic studies, making this group one of the least unknown in chromosomal terms. In this study, the BAC-FISH technique was used to investigate the organization and evolutionary status of microchromosomes in bird species from the orders Passeriformes and Charadriiformes. The results revealed a high degree of conservation in the evolution of the karyotype of the Passeriformes, despite the fact that they are considered a highly derived group in the phylogeny of birds. On the other hand, in the Charadriiformes analyzed species, each showed a distinct evolutionary path, with microchromosome reorganization events. Two new chromosome numbers were also described for the species Calidris canutus (2n = 92) and Troglodytes aedon (2n = 76). These findings highlight the evolutionary differences between the two orders of birds, suggesting that the Charadriiformes may be subject to more varied or intense selective pressures that lead to greater diversity in chromosome organization.